Compressive strength measurement for cement replacement with recycled glass in concrete - Khalil, Asmaa S. (Iraqi Journal of Physics, 2019)
The most important environmental constraints at the present timeis the accumulation of glass waste (transparent glass bottles). A lot ofexperiments and research have been made on waste and recyclingglass to get use it as much as possible. This research using recyclingof locally waste colorless glass to turn them into raw materials asalternative of certain percentages of cement to save the environmentfrom glass waste and reduce some of the disadvantages of cementwith conserving the mechanical and physical properties of concretemade. A set of required samples were prepared for mechanical testwith different weight percentage of waste glass (2%, 4%, 5%, 6%,8%, 10%, 15%, 20% and 25%). American standard for calibration(ASTM C109 / C109M-02) to measure the compressive strengthwhere the results showed that the Maximum compressive strengthwas obtained at the low weight percentage replacement 2%, 4% and5% 6% which is 67.12, 69.24, 62.56 and 59.96 Mpa respectively. fororiginally mix recorded bending resistance (54.16) Mpa.